Initial evaluation of low-dose phenobarbital as an indicator of compliance with antimalarial drug treatment. - Karbwang, J. (World Health Organization, 1998)
Since poor compliance with antimalarial therapy is often suspected but difficult to prove, this study attempted to establish a model for predicting the plasma concentration of phenobarbital (given in low doses in conjunction with the drug) as an indicator of compliance. Phenobarbital was chosen because its value had been demonstrated as a marker of compliance in long-course therapies, any significant departure from steady-state concentrations (achieved with full compliance) indicating one or more missed doses. Therapy for uncomplicated malaria varies from 5 days with artesunate to 7 days with quinine + tetracycline. Volunteers with confirmed falciparum malaria were randomized into 5 groups and given malaria therapy as well as phenobarbital daily for 3-7 days. Plasma samples for determination of phenobarbital concentrations were taken just prior to the daily dose of phenobarbital. Although there was a clear and predictable individual pattern of blood concentrations following each dose of phenobarbital, inter-individual variation in blood levels was significant and reduced their predictive value beyond the second day's dose. The cause of the variations is not clear; it could be attributable to different sources of the drug, previous intake of phenobarbital by the patient, or differences in drug absorption and disposition in malaria patients. Results for the 5-day artesunate regimen suggest that phenobarbital may be useful as a marker of compliance if the patient stops medication after 3 days; clear differences were evident at the end of the course of treatment between plasma phenobarbital concentrations in individuals completing the 5-day course and those who stopped after 3 days. For the quinine-tetracycline regimen, results suggest that it may be possible to discriminate between subjects where there is a 3-day difference in treatment. Phenobarbital is a better discriminant when dosing is every 24 hours as with artesunate, rather than the 8-hourly regimen for quinine-tetracycline. When measuring compliance for malaria treatment, if it is important to know what proportion of patients reach 3, 5 or 7 days of compliance, then phenobarbital might have a role to play in this assessment, but further investigations in more patients would be required. Alternatively, different markers could be used for the doses to be given on these days and, as long as the patient does not mix the doses for the different days, sequential doses and determination of compliance could be based on an "all or none" detection of the marker rather than on drug levels.